2015 Science and Information Conference (SAI) 2015
DOI: 10.1109/sai.2015.7237283
|View full text |Cite
|
Sign up to set email alerts
|

Promote the industry standard of smart home in China by intelligent router technology

Abstract: The reason why smart home remains not popularized lies in bad product user experience, purchasing cost, and compatibility, and a lack of industry standard[1]. Echoing problems above, and having relentless devoted to software and hardware innovation and practice, we have independently developed a set of solution which is based on innovation and integration of router technology, mobile Internet technology, Internet of things technology, communication technology, digital-to-analog conversion and codec technology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Among them, →4)-α-IdoA2S-(1→4)-α-GlcNS6S-(1→ accounts for the highest proportion. It is also the major disaccharide structure of mammalian heparin [34]. Compared with the previous literature [26,30,35], it is clear that the same anomeric signals are present in C. antiquata heparin analogues and mammalian heparin.…”
Section: Nmr Spectroscopy Analysissupporting
confidence: 53%
“…Among them, →4)-α-IdoA2S-(1→4)-α-GlcNS6S-(1→ accounts for the highest proportion. It is also the major disaccharide structure of mammalian heparin [34]. Compared with the previous literature [26,30,35], it is clear that the same anomeric signals are present in C. antiquata heparin analogues and mammalian heparin.…”
Section: Nmr Spectroscopy Analysissupporting
confidence: 53%
“…It is consumers' perception of the time and energy required to operate smart homes easily and skillfully based on their acquired knowledge and experience. Compatibility issues, which are often mentioned in various studies (Bao et al 2014;Lin et al 2015), are also among the factors in the category of perceived ease of use. And perceived cost is always seen as a social barrier in the diffusion and promotion of smart homes (Balta-Ozkan et al 2013a, b;Lin et al 2015;Ehrenhard et al 2014)…”
Section: Identification Of Key Influential Factors Of Consumer Adoption Of Smart Homesmentioning
confidence: 99%
“…It is an external factor that facilitates consumer adoption of smart homes. Studies (Coughlin et al 2007;Lin et al 2015;Ehrenhard et al 2014) have revealed that governments should regulate the market, because the implementation of a unified industry standard encourages market innovation, and play the role of supervisor in the diffusion of smart homes. Chan et al (2008) indicated that legal and ethical issues are future challenges bearing the same importance as factors such as acceptability, reliability, and cost.…”
Section: (3) Enterprise Dimensionmentioning
confidence: 99%